2015
DOI: 10.1021/acs.inorgchem.5b01278
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Metal Strategy on Metal–Organic Frameworks (MOFs) for Functionalities Expansion: Co Substitution Induces Aerobic Oxidation of Cyclohexene over Inactive Ni-MOF-74

Abstract: Different amounts of Co-substituted Ni-MOF-74 have been prepared via a post-synthetic metal exchange. Inductively coupled plasma mass spectrometry, powder X-ray diffraction (XRD), N2 adsorption/desorption, and extended X-ray absorption fine structure (EXAFS) analyses indicated the successful metathesis between Co and Ni in Ni-MOF-74 to form the solid-solution-like mixed-metal Co/Ni-MOF-74. It was found that introduction of active Co into the Ni-MOF-74 framework enabled the inert Ni-MOF-74 to show activity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(128 citation statements)
references
References 34 publications
2
118
0
Order By: Relevance
“…Figure shows the Ni K‐edge X‐ray absorption near‐edge structure (XANES) and Fourier transformation of the extended X‐ray absorption fine structure (FT‐EXAFS) spectra of Ni‐MOF‐74‐T with reference samples. In the XANES spectra, the shape of Ni‐MOF‐74 before heat treatment was similar to that of NiO and Ni(NO 3 ) 2 , indicating Ni species in the Ni‐MOF‐74 network were present as Ni 2+ ions . The FT‐EXAFS spectrum for Ni‐MOF‐74 showed a strong absorption peak at around 1.7 Å, which was derived from the Ni−O bonds in the Ni cluster, and a second peak at around 2.7 Å attributed to neighboring Ni atoms (Ni‐O‐Ni bonds) .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Figure shows the Ni K‐edge X‐ray absorption near‐edge structure (XANES) and Fourier transformation of the extended X‐ray absorption fine structure (FT‐EXAFS) spectra of Ni‐MOF‐74‐T with reference samples. In the XANES spectra, the shape of Ni‐MOF‐74 before heat treatment was similar to that of NiO and Ni(NO 3 ) 2 , indicating Ni species in the Ni‐MOF‐74 network were present as Ni 2+ ions . The FT‐EXAFS spectrum for Ni‐MOF‐74 showed a strong absorption peak at around 1.7 Å, which was derived from the Ni−O bonds in the Ni cluster, and a second peak at around 2.7 Å attributed to neighboring Ni atoms (Ni‐O‐Ni bonds) .…”
Section: Resultsmentioning
confidence: 90%
“…Ni‐MOF‐74 was prepared using the following procedure . Ni(NO 3 ) 2 ⋅ 6 H 2 O (4.756 g) and 2,5‐dihydroxyterephthalic acid (0.956 g) were added into of a mixture of water, ethanol and DMF (400 mL with a molar ratio of 1:1:1).…”
Section: Methodsmentioning
confidence: 99%
“…However, often the size difference of the incorporated metals is rather small and therefore significant shifts of the corresponding reflections are difficult to observe with standard XRD setups. However, by using high‐resolution XRD measurements valuable information could be obtained for certain systems …”
Section: Mixed‐metal Metal–organic Frameworkmentioning
confidence: 99%
“…The engineering of MM‐MOFs can lead to new frameworks with novel or multiple functions improving catalytic or gas sorption performance. Previous studies have shown the properties of several synthesized MM‐MOFs …”
Section: Introductionmentioning
confidence: 99%
“…Mixed‐metal MOFs were found to be potential heterogeneous catalysts with better catalytic performance compared with the analogous single‐metal MOFs. This superior performance is due to bi‐ and multi‐functional active catalytic sites that can promote reactions that require more than one type of site . For instance, NH 2 ‐UiO‐66(Zr/Ti) showed enhanced photocatalytic activity under visible light .…”
Section: Introductionmentioning
confidence: 99%